A Guideline and Checklist for Initiating and Managing Clozapine Treatment in Patients with Treatment-Resistant Schizophrenia - Correll, C. U.; Agid, Ofer; Crespo-Facorro, Benedicto; de Bartolomeis, Andrea; Fagiolini, Andrea; Seppälä, Niko; Howes, Oliver D. (CNS drugs, 2022)
Treatment-resistant schizophrenia (TRS) will affect about one in three patients with schizophrenia. Clozapine is the only treatment approved for TRS, and patients should be treated as soon as possible to improve their chances of achieving remission. Despite its effectiveness, concern over side effects, monitoring requirements, and inexperience with prescribing often result in long delays that can expose patients to unnecessary risks and compromise their chances of achieving favorable long-term outcomes. We critically reviewed the literature on clozapine use in TRS, focusing on guidelines, systematic reviews, and algorithms to identify strategies for improving clozapine safety and tolerability. Based on this, we have provided an overview of strategies to support early initiation of clozapine in patients with TRS based on the latest evidence and our clinical experience, and have summarized the key elements in a practical, evidence-based checklist for identifying and managing patients with TRS, with the aim of increasing confidence in prescribing and monitoring clozapine therapy.